Shopping well-being through mobile apps: A congruence theory perspective - Kamel El Hedhli (17100172) (2025)
We build on theories from social psychology and retailing to investigate how shopping apps become part of shoppers' identities, and ultimately influence their sense of well-being as well as relevant retailing outcomes. Specifically, drawing on the congruence theory, this research advances that, beyond the retail apps' functional utility, shoppers are drawn to shopping apps that align with their personal identities in terms of self-congruity and lifestyle congruence. These distinct app-related congruities are hypothesized to be associated with shoppers' well-being. Specifically, functional congruence, self-congruity, and lifestyle congruence with a retail app are expected to exhibit differential associations with shopping well-being. In addition, self-congruity and lifestyle congruence are expected to amplify the association between functional congruence and shopping well-being. The sense of well-being experienced when shopping through retail apps is, in turn, likely to be associated with important retailing outcomes. Survey data were collected from mobile shoppers using fashion retail apps in two culturally distinct markets—the United States and Japan—to enhance the generalizability of the findings. The results of a SmartPLS-based SEM provide support for the hypothesized associations. Along with functional congruence, identity-based congruities are positively associated with shoppers’ well-being. In particular, shopping well-being shows a stronger association with self-congruity than with functional congruence. Additionally, shopping well-being is positively associated with favorable attitudes toward the app, intentions of continuance app use, and retailer loyalty. This paper provides valuable insights for mobile retailers by advancing our understanding of how shopping apps shape shopper identity and well-being. Other Information Published in: Journal of Retailing and Consumer Services License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jretconser.2025.104545